2008
DOI: 10.3928/15428877-20080301-02
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Glue in Sutureless Vitreoretinal Surgery for the Treatment of Wound Leakage

Abstract: The results demonstrated the efficacy of tissue glue for closing site ports when wound leakage is observed in transconjunctival sutureless vitreoretinal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…This is usually a simple maneuver, but it can lead to some undesirable effects, such as astigmatism and foreign body sensation, and sometimes it could be difficult to place because of chemosis or bleeding. 29 Alternative techniques, such as tissue glues [30][31][32] and polyethylene glycol-based hydrogel bandaging, 33 have been proposed but are not currently used. Releasable suture placement has been described, 34 although it requires release at the slit lamp on the first postoperative day, which can be difficult to perform when scleral or conjunctival bleeding occurs.…”
Section: Discussionmentioning
confidence: 99%
“…This is usually a simple maneuver, but it can lead to some undesirable effects, such as astigmatism and foreign body sensation, and sometimes it could be difficult to place because of chemosis or bleeding. 29 Alternative techniques, such as tissue glues [30][31][32] and polyethylene glycol-based hydrogel bandaging, 33 have been proposed but are not currently used. Releasable suture placement has been described, 34 although it requires release at the slit lamp on the first postoperative day, which can be difficult to perform when scleral or conjunctival bleeding occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that adhesives such as cyanoacrylate and fibrin glue were ineffective for use in sclerotomy closure [46] Although N -isopropylacrylamide monomer is toxic to neural tissue, after polymerization, the pNIPAM molecule is no longer toxic. It is commonly used, for example, in cell and tissue cultures for its reversible cell adhesion properties.…”
Section: Discussionmentioning
confidence: 99%
“…Bioadhesives such as cyanoacrylate and fibrin glue have been used to close leaking sclerotomies after vitrectomy surgery. However, the use of these compounds resulted in complications such as incomplete sclerotomy closure, ocular hypotony and surface roughness leading to ocular irritation [46]. …”
Section: Introductionmentioning
confidence: 99%
“…Fibrin tissue adhesives are an effective method for opposing wound edges and their use in ophthalmic surgery has broadened. [25][26][27][28] Fibrin glue has been used previously to focally repair bleb leaks, but not as an adjunct to suturing during conjunctival advancement bleb repair. The aim of this paper is to present a series of patients undergoing bleb repair using bleb preservation, conjunctival flap, and fibrin glue.…”
Section: Introductionmentioning
confidence: 99%